Climate stability across the Eocene-Oligocene transition, southern Argentina - Kohn, Matthew J. (2004)
Fossil mammal teeth from mid-latitude southern Argentina (∼46°S) that closely bracket the Eocene-Oligocene transition show no resolvable change in oxygen isotope compositions. In combination with paleofloral observations and geographic considerations, this finding implies not only that climate was essentially constant, despite interpretations elsewhere for major mid- and high-latitude cooling, but also that evolution of hypsodonty did not coincide with climate change during the Eocene-Oligocene transition. One possible explanation for Eocene-Oligocene transition climatic stability is that southern high-latitude cooling increased latitudinal temperature gradients and strengthened ocean circulation gyres, including the southward-flowing Brazil Current in the western South Atlantic. Regionally increased heat transport in the western Atlantic offset global cooling, producing a nearly constant temperature in southern South America. A more radical interpretation, supported by some marine data, is that the paradigm of major global cooling at the Eocene-Oligocene transition is largely false, in that mean sea-surface temperatures changed very little.